Penerapan Virtual Reality Tour sebagai Media Informasi pada Yayasan Pendidikan - Yoga Handoko Agustin; Siti Nurendah (Institut Teknologi Garut, 2026)
The development of information technology has driven innovation in information delivery, one of which is through Virtual Reality Tours (VR Tours). This study aims to implement a VR Tour as an information medium at the Assalafiyah II Educational Foundation in Cibiuk, Garut, so that the public, prospective students, and parents can explore the foundation’s environment interactively without having to visit the location directly. The method used is the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The data were obtained through 360° panoramic photographs, text, and supporting multimedia, which were then integrated using 3DVista software. The results show that panoramic navigation, information on educational units, galleries, location maps, and social media links function properly. The resulting application is web-based and can be accessed via computers and smartphones. With the implementation of this VR Tour application, the Assalafiyah II Foundation can expand its information reach while enhancing its appeal to prospective students and the general public.